Outcomes of Posterior Wall Thickness, Interventricular Septal Thickness and LA diameter after Surgical Closure of Ventricular Septal Defect in Different Age Group - Aminullah, Md; Sarker, Swadesh Ranjan; Hasan, Rakibul; Rahman, Mahbubur; Hoque, Rezwanul (University Heart Journal, 2017)
Background: Good outcome after surgical closure of ventricular septal defect is essential. Objective: The purpose of the present study was to see the improvement of posterior wall thickness, interventricular septal thickness and LA diameter after surgical closure of ventricular septal defect in different age group. Methodology: This prospective cohort studies was conducted in the Department of Cardiac Surgery at National Institute of Cardiovascular Disease (NICVD), Dhaka. Patient with surgical closure of VSD were enrolled into this study purposively and were divided into 3 groups according to the age. In group A (n=10), patients were within the age group of 2.0 to 6.0 years; age of group B (n=8) patients were 6.1-18.0 years and the group C (n=6) ages range was 18.1-42.0 years. Echocardiographic variables such as posterior wall thickness, interventricular septal thickness and LA diameter were taken preoperatively and at 1st and 3rd month of postoperative values. Result: Totally 24 patients were recruited for this study. The mean age was 12.60±12.09. After 1 month posterior wall thickness was increased by 12.07%, 7.02% and 5.26% in group A, group B and group C respectively. After 3 months left ventricular posterior wall thickness was decreased by 36.21%, 29.78% and 17.58% in group A, group B and group C respectively. After 1 month interventricular septal thickness was increased by 3.51%, 8.86% and 9.22% in group A, group B and group C respectively. After 3 months interventricular septal thickness was decreased by 31.58%, 25.00% and 16.67% in group A, group B and group C respectively. After 1 month LA diameter was increased by 4.81%, 4.28% and 4.75% in group A, group B and group C respectively. After 3 months LA diameter was decreased by 15.93%, 12.84% and 5.96% in group A, group B and group C respectively. Conclusion: Cardiac remodeling occurred after surgical closure of ventricular septal defect and remodeling were more significant in younger age group. University Heart Journal Vol. 12, No. 1, January 2016; 12-16